2012
DOI: 10.1097/prs.0b013e3182547e22
|View full text |Cite
|
Sign up to set email alerts
|

A Standardized Operative Team for Major Head and Neck Cancer Ablation and Reconstruction

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 9 publications
0
36
1
1
Order By: Relevance
“…Despite a statistically significant decrease in operative and ischemia time among groups, we did not find a statistically significant difference in surgical complications, flap viability, flap outcomes, or need for reoperation among the groups, which speaks to the uniformity in the surgical aspects of care among the study population and supports the notion that the observed differences are a reflection of the changes in perioperative management. Longer operative and ischemia times have been related to increased LOS and complications . A recent prospective analysis on major head and neck surgeries (not restricted to free flap patients) suggested that operative time >220 minutes was associated with prolonged LOS .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite a statistically significant decrease in operative and ischemia time among groups, we did not find a statistically significant difference in surgical complications, flap viability, flap outcomes, or need for reoperation among the groups, which speaks to the uniformity in the surgical aspects of care among the study population and supports the notion that the observed differences are a reflection of the changes in perioperative management. Longer operative and ischemia times have been related to increased LOS and complications . A recent prospective analysis on major head and neck surgeries (not restricted to free flap patients) suggested that operative time >220 minutes was associated with prolonged LOS .…”
Section: Discussionmentioning
confidence: 99%
“…Longer operative and ischemia times have been related to increased LOS and complications. [28][29][30] A recent prospective analysis on major head and neck surgeries (not restricted to free flap patients) suggested that operative time >220 minutes was associated with prolonged LOS. 30 Ischemia time >5 hours has been correlated to higher complication rates and partial flap loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Es importante tener en cuenta la curva de aprendizaje de esta técnica para conseguir resultados fiables. Aunque no hay cifras exactas, la experiencia adquirida a partir de la realización de 30-50 CLM permite obtener resultados óptimos 11 . En nuestra serie, el número de intervenciones ha aumentado progresivamente con el paso de los años, hasta estabilizarse, permitiendo incorporar la técnica al arsenal terapéutico habitual y ampliar las indicaciones.…”
Section: Discussionunclassified
“…The entire operative team can affect the procedure duration. One study 9 sought to specifically evaluate the effect of the nursing team on procedure length by instituting a standardized OR nursing team for free flaps. The researchers compared the procedure lengths before and after the introduction of consistent nursing team members who were familiar with all aspects of the procedure.…”
Section: Procedures Overviewmentioning
confidence: 99%